Implementasi Implementasi Teknologi Solar Biodigester dan Bioaktivator dalam Upaya Reduksi Sampah Organik di Madrasah Aliyah Pondok Pesantren Mu’allimin Kabupaten Agam : Enhanced Management of Organic Waste through Solar Biodigester Technology and Bioactivators at Madrasah Aliyah Pondok Pesantren Mu’allimin, Tilatang Kamang District, Agam Regency - Tetra, Olly Norita; Refilda, Refilda; Zein, Rahmiana; Safni, Safni; Emriadi, Emriadi; Imelda, Imelda; Deswati , Deswati; Zulhadjri , Zulhadjri (Jurnal Hilirisasi IPTEKS, 2026)
Organic waste from food scraps is a major contributor to environmental pollution. The Madrasah Aliyah at the Mu’allimin Islamic Boarding School generates approximately 15–20 kg of organic waste per day, which is directly disposed of in a temporary storage area without any treatment. This has the potential to cause odors, environmental pollution, and health hazards. Therefore, food waste management is necessary to address these issues. One method of waste management is solar biodigester technology combined with bioactivators, which is a simple, inexpensive, and easy-to-implement technology. This community service activity aims to apply solar biodigester technology combined with bioactivators to reduce organic waste. Success indicators include a reduction in the volume of organic waste, the production of solid and liquid compost, accelerated degradation time, and increased understanding among participants. The method used is Participatory Approach through stages of outreach, training in the construction and operation of solar biodigesters, and practical sessions on bioactivator production. Evaluation was conducted by measuring waste volume before and after treatment, observing the degradation process, and assessing participants’ level of understanding. The results showed that the application of solar biodigester and bioactivator technology was able to reduce kitchen waste volume by 50.8% with a faster degradation time compared to conventional methods, and participants’ knowledge increased by 52.68%. The integration of solar biodigesters and bioactivators is effective in reducing organic waste, accelerating degradation, conserving land, and being environmentally friendly.